EPS & EPUS Step-size Control for Linear Multistep Method - Abbas Al-Bayati; Ann Al-Sawoor; Abbas Taqi (Al-Rafidain Journal of Computer Sciences and Mathematics)
In this paper we consider step-size control in one class of Adams linear multi-step methods for Ordinary differential equation.   Theoretical results are presented for Adam-Bashforth-Moulton formula using both Error-per-step (EPS)  & Error-per-Unit -Step (EPUS) controls. These obtained by considering a 2D system of the form: